Analysis on the Market influencing factors of Laos attracting Chinese Enterprises to start a Business in Laos - Philakone Chindavong (SHS Web of Conferences, 2023)
With the gradual deepening of the initiative of the Belt and Road Initiative, the scale of China’s investment in Laos has also expanded. The domestic investment environment in Laos continues to improve, and international cooperation is deepening. Both products and technologies have flooded into the Lao domestic market, which has had a huge impact and impact on the development of Laos’ local economy. At the same time, Chinese companies choosing to invest and start businesses in the domestic market of Laos can expand the income sources of Chinese companies, increase the international reputation of Chinese companies, and promote social development. With the continuous strengthening of China-Laos cooperation in various fields, Laos has also taken some measures to attract Chinese companies to invest and start businesses in Laos, and China-Laos cooperation has reached a new level. However, due to the lack of economic growth in Laos and the lack of a comprehensive industrial sector, there are many problems in the investment environment. If Laos fails to take effective measures, it is likely to harm Chinese companies investing in Laos. Therefore, Chinese companies pay great attention to the industries of large regional and regional companies in Laos, which are closely related to the climate and market conditions in Laos.